Optimization of Social Media as Media Promotion of Historial Tourist Destination in Surabaya - Prida Ariani Ambar Astuti; Muhammad Iqbal Athallariq; Alifia Widya Febbyani; Jihan Shohwatul Islamiyah; Dwiky Nurfiansyah; Teguh Satria Ode Putra (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
At the end of 2019, Kampung Lawang Seketeng was designated by the Surabaya City Government as a heritage tourism destination because it is the oldest village in Surabaya and has a legacy for the Indonesian people in the form of the childhood home of the first President of the Republic of Indonesia, Ir. Soekarno. Unfortunately, although it was reorganized and reconstructed to become a tourist spot, the number of tourists visiting has stayed the same. The results of the pre-Community Service research identified the problem faced by the Kampung Lawang Seketeng Tourism Board: they need to optimize social media as a promotional medium. At the same time, messages distributed by social media have the potential to reach a vast and diverse audience. Social media is also believed to empower users to become new influencers. Therefore, it is necessary to create social media accounts, take photos, and make profile videos uploaded on social media. Also, it is essential to conduct training on social media management, photography, and digital marketing so that tourists are aware, interested, and finally persuaded to visit Kampung Lawang Seketeng as a tourist heritage destination in Surabaya.